Radikalisme Islam: Telaah Kampanye Khilafah oleh Hizbut Tahrir Indonesia (HTI) Pra-Pembubaran oleh Pemerintah - M. Kautsar Thariq Syah; Paelani Setia (Jurnal Iman dan Spiritualitas, 2021)
This paper will discuss the Khilafah ideological campaign by Hizbut Tahrir Indonesia (HTI) before the revocation of operational permits by the government in 2017. The opening of the tap for democratization after the fall of the New Order regime led to the proliferation of new mass organizations, including religious organizations. HTI entered Indonesia in the 1980s because of the opportunities due to the opening of the faucet of democracy. They are aggressively carrying out large-scale campaigns to ground their ideology and ideals, namely forming an Islamic state (Khilafah Islamiyah). HTI cleverly campaigns for the caliphate ideology through their significant events, namely in conferences, leaders' conferences, and the My Movement plan for teenagers. In addition, HTI also campaigns for a caliphate through print media, namely Al-Islam, Al-Wa-ie', and Media Ummat. In responding to the challenges of the times, HTI uses social media as another campaign instrument. They also managed to “advertise” their young figures who became new role models for Islam among the millennial generation through social media. The revocation of operational permits by the government marked the end of the offline HTI campaign, although their struggles on social media did not stop. Social media with the principle of openness became the main instrument of HTI's campaign after the government dissolved it.